1987
DOI: 10.1007/bf00252601
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and experimental study of respiratory motion effect on image quality of single photon emission computed tomography (SPECT)

Abstract: The effect of respiratory motion on the image quality of single photon emission computed tomography (SPECT) was investigated by computer simulation and experimentation. In the computer simulation, the phantom was assumed to be cylindrical with a uniform background and a spherical cold or hot spot. To simulate respiratory motion, a cyclic linear motion parallel to the axis of rotation of a gamma camera was assumed. The contrast in the transaxial images was calculated for various respiratory amplitudes and its d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 7 publications
0
11
0
1
Order By: Relevance
“…The respiration artefact is a well known source of error in the quantification of the GSPECT images [15]. GSPECT is used to assess the myocardial perfusion and function and the respiratory motion potentially affects both types of quantifications [16,17]. It is already shown that changes in the attenuation due to movement of the heart and diaphragm during respiration may cause lower count density in inferior wall [6,18] that may be augmented by abdominal activity distribution [19].…”
Section: Discussionmentioning
confidence: 98%
“…The respiration artefact is a well known source of error in the quantification of the GSPECT images [15]. GSPECT is used to assess the myocardial perfusion and function and the respiratory motion potentially affects both types of quantifications [16,17]. It is already shown that changes in the attenuation due to movement of the heart and diaphragm during respiration may cause lower count density in inferior wall [6,18] that may be augmented by abdominal activity distribution [19].…”
Section: Discussionmentioning
confidence: 98%
“…Respiratory motion is known to cause artifacts and decrease the tumor detectability in medical imaging [1,2]. In some imaging modalities it is possible to acquire a complete study of the chest during a single breath hold.…”
Section: Introductionmentioning
confidence: 99%
“…The images of the whole thorax is impractical which requires multiple breathhold sets of contiguous spiral scans to cover the thorax completely with single-detector row CT (10). Respiratory motion is known to cause artifacts, which decrease tumor detectability, and alter quantification of localization in medical imaging (11)(12)(13). The radiologists' variable experience and perception capacity also greatly influence the accuracy of detection (14).…”
Section: Review Articlementioning
confidence: 99%